Effect of a pharmacist managed smoking cessation clinic on quit rates - Philbrick AM; Newkirk EN; Farris KB; McDanel DL; Horner KE (Centro de Investigaciones y Publicaciones Farmaceuticas, 2009)
Objective: The purpose of this study was to quantify quit rates, determine factors predicting success, and analyze patients' perceptions at 3 months after participation in the pharmacist-managed Smoking Cessation Group Clinic.Methods: This was a prospective, single group study that was conducted in patients that had participated in the Smoking Cessation Group Clinic at the University of Iowa Hospitals and Clinics. Clinic participants received structured group counseling covering various topics associated with cessation. Varenicline, bupropion and nicotine replacement therapy were used as smoking cessation aids and selection was based on patient preference and absence of contraindications. The primary outcome of this trial was smoking status at 3 months. The patients were contacted by telephone at 3, and 6 months after the start of the clinic and asked about current smoking status. At 3 months, patients were asked to rate on a Likert scale of 1 to 5 (1=not helpful; 5=very helpful) their perceptions of individual aspects of the clinic and on a scale of 1 to 10 (1=not helpful; 10=very helpful) how they perceived their cessation aid. Results: From February 2007 to January 2008, 21 patients enrolled in the intent-to-treat follow up study. Analysis of data was completed in August 2008. At 3 and 6 months, 47.6% and 52.4%, of patients reported being smoke-free, respectively. At 3 months, factors consistent with success included having more previous quit attempts and type of cessation aid used. These endpoints continued to be significant at 6 months, in addition to attending more clinic sessions, and type of insurance (favoring private insurance). Patients who quit smoking rated their cessation aid as more helpful than those who did not quit smoking (8.56; SD=0.88 verses 6.71; SD=2.81, respectively; p=0.14). The aspect of the clinic most helpful to patients was group interaction (4.53; SD=0.77). Conclusion: This study demonstrates that pharmacists can play a vital role with smoking cessation in a group setting. Group setting patient counseling can be an effective tool for pharmacists to reach more people within the same time frame as individual counseling.